Introduction - Tomáš Kasper; Karel Rýdl; Andreas Hoffmann-Ocon (Charles University, 2018)
The monothematic issue of Pedagogika, Historical Reflection of Education and Its Significance in (Not Only) Teacher Education, tackles several questions and problematic areas at a time.